Lewis Acid Mediated Cyclizations: Diastereoselective Synthesis of Six- to Eight-Membered Substituted Cyclic Ethers - Ghosh, Arun K.; Tomaine, Anthony J.; Cantwell, Kelsey E. (Synthesis, 2017)
Cyclic ethers are widely abundant in natural products. Cyclic ether templates are also utilized in drug design and medicinal chemistry. Although the synthetic processes for this class of compounds have been studied extensively with respect to five- and six-membered rings, medium-sized cyclic ethers are synthetically more challenging due to a variety of factors. Herein, we report our results on the Lewis acid catalyzed synthesis of medium-sized cyclic ethers in a diastereoselective manner.
Keywords: cyclization; cyclic ethers; diastereoselectivity; Lewis acids; oxacycles; oxepanes; oxocenes; polycycles